Synthesis and Spectral Studies of ZrO(II) Complexes with Aroylhydrazones - Angadi, S.D.; Kulkarni, V.H. (Asian Journal of Chemistry, 2010)
Complexes of zironium(IV) with aroylhydrazones have been prepared in methanolic medium. The complexes have the stoichiometry of the type ZrOCl2L2. These are yellow to orange amorphous substances and are soluble in methanol, ethanol and DMF. The spectral data suggest that the oxygen of carbonyl group and nitrogen of azomethine group are involved in coordination. These ligands behaves as bidentates and a coordination number of seven has been proposed for zirconium in these complexes.